Respiration, microbial biomass and soil phosphatase activity in two agroecosystems and one forest in Turrialba, Costa Rica - Durango, Wuellins (2015)
In order to evaluate some microbiological and biochemical characteristics, a comparative study was carried out, as related to 3 different land uses in Ultisols located in Grano de Oro, Turrialba, Costa Rica. Three soil management systems were selected (two agroecosystems, coffee and coffee-banana) and forest. In each farm, 4 composite soil samples were collected, on which microbial biomass and respiration, and phosphatase enzyme activity analysis were performed. The microbial biomass in forest was statistically higher (423 mg C kg-1) compared to those in agroecosystems coffee and coffee-banana (77 and 111 mg C kg-1 respectively). Microbial respiration did not show differences due to land management (580, 560 and 570 μg CO2 g-1.day-1 in coffee, coffee-banana and forest systems, respectively). It was also determined that the enzyme phosphatase activity in forest soils was statistically higher (4432 μg p-NP g-1.h-1). The data suggest that soil conditions in the forest favor greater microbial activity and phosphatase biomass, as compared to agricultural systems.